Urinary Modified Nucleosides as Novel Biomarkers for Diagnosis and Prognostic Monitoring of Urothelial Bladder Cancer. Issue 6 (November 2014) - Zhang, Yu-Rui; Shi, Lei; Wu, Hui; Tang, Dong-Dong; Wang, Shao-Min; Liu, Hong-Min; Zhang, Li-Rong; Song, Dong-Kui
Aims and background: To ascertain the value of the detection of urinary modified nucleosides in the early diagnosis and prognostic monitoring of urothelial bladder cancer. Methods: One hundred seventeen patients with urothelial bladder carcinoma and 66 healthy volunteers were included in the study. High-performance liquid chromatography/electrospray ionization quadrupole time-of-flight mass spectrometry (HPLC/ESI-Q-TOF-MS) was used to measure the levels of urinary modified nucleosides in the bladder cancer and control groups. Postoperative monitoring was done every 3 months in patients with noninvasive carcinoma; 85 patients attended the 1-year follow-up visit. Results: The levels of m1A, ac4C, O6-MeG and 1-MeI were significantly higher in cases than controls (P <0.05). The highest sensitivity (92.45%) and specificity (87.50%) were obtained when 1-MeI detection was combined with m1A detection. The m1A and 1-MeI levels 3 months after operation in both patient groups were significantly lower than the preoperative levels (P <0.01). The no-recurrence group subsequently maintained low levels, but in the recurrence group the levels rose again almost to preoperative values. At 6, 9 and 12 months after operation, the m1A and 1-MeI levels of the recurrence group were higher than those of the no-recurrence group and the control group (P <0.01). Conclusions: Urinary modified nucleosides might become novel tumor markers that will facilitate the clinical management and will be helpful in the diagnosis and follow-up of urothelial bladder cancer. m1A and 1-MeI appear to be most promising for clinical use and be worthy of further study in the near future.